2003
DOI: 10.1007/s00113-002-0542-0
|View full text |Cite
|
Sign up to set email alerts
|

Nachweis einer radiographisch okkulten Osteochondrosis dissecans tali mit der MRT

Abstract: Posttraumatic disorders of the ankle are a common cause of chronic pain. Magnetic resonance imaging (MRI) has proved to be highly useful in clarifying a wide spectrum of underlying lesions which frequently cannot be detected on radiographs. Even if the assessment of the lateral collateral ligaments of the ankle is not regarded as a primary indication for MRI, it allows the diagnosis of subchondral contusions or cysts, anterolateral impingement syndrome, sinus tarsi syndrome, osteochondral fractures and osteoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thus, they recommended fast spin-echo proton density-weighted and T 2 weighted MR sequences to evaluate the articular cartilage integrity and lesion stability. On the other hand, Wirth et al 14 demonstrated that MR enabled the detection of an OCD case (confirmed upon arthroscopy) not diagnosed on plain films, although a superficial cartilage defect, as shown on arthroscopy, was not detected on the MR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they recommended fast spin-echo proton density-weighted and T 2 weighted MR sequences to evaluate the articular cartilage integrity and lesion stability. On the other hand, Wirth et al 14 demonstrated that MR enabled the detection of an OCD case (confirmed upon arthroscopy) not diagnosed on plain films, although a superficial cartilage defect, as shown on arthroscopy, was not detected on the MR.…”
Section: Discussionmentioning
confidence: 99%